A solid oxide fuel cell fuelled by methane recovered from groundwater. (1st April 2021) - Saadabadi, S. Ali; van Linden, Niels; Heinsbroek, Abel; Aravind, P.V.
Abstract: This study investigates the feasibility of electricity production in a solid oxide fuel cell using methane recovered from groundwater as the fuel. Methane must be removed from groundwater for the production of drinking water to, amongst others, avoid bacterial regrowth. Instead of releasing methane to the atmosphere or converting it to carbon dioxide by flaring, methane can also be recovered by vacuum stripping and served as a fuel. However, the electrical efficiency of currently used combustion-based technologies fuelled with methane-rich gas is limited to 35% due to the low heating value of the recovered gas (70 mol. % methane) and power derating due to the presence of carbon dioxide (25 mol.%). We propose to use a solid oxide fuel cell to use the methane-rich gas as fuel. Solid Oxide Fuel Cells are fuel-flexible and potentially attain higher electrical efficiencies up to 60%. To this end, specific gas processing, including cleaning and methane reforming, is required to allow for durable operation in a solid oxide fuel cell. We assessed whether electricity could be generated by a solid oxide fuel cell using methane recovered from a full-scale drinking water treatment plant as a fuel. The groundwater had a methane concentration of 45 mg∙L -1, and the recovered gas by vacuum towers contained 70 mol% methane. We used a gas cleaning reactor with impregnated activated carbon to remove hydrogen sulfide traces from the methane-rich gas. Thermodynamic calculations showed that additional steam is required to achieve a high methane reforming. The added steam and the carbon dioxide content in the recovered gas simultaneously contribute to the methane reforming to prevent carbon deposition. The measured open circuit potential corresponded with the theoretical Nernst voltage, implying high methane reforming in the solid oxide fuel cell. The achieved power density of the cell fuelled with the methane-rich gas (mixed with steam) was 27% less than the hydrogen-fuelled cell. Ultimately, 51.2% of the power demand of the plant can be covered by replacing the gas engine in a drinking water treatment with a 915 kW solid oxide fuel cell system fuelled by the methane recovered from the groundwater, while the greenhouse gas emission can be reduced by 17.6%. Graphical abstract: Image 1 Highlights: Methane recovered from groundwater is used as a fuel for solid oxide fuel cells. Impregnated activated carbon is used to remove traces of hydrogen sulfide from fuel. Required steam to achieve a high rate of methane reforming is determined. The cell performance with internal methane reforming is experimentally investigated. The sustainability of the groundwater treatment plant can be improved by applying an SOFC system.